Turkey : Request for Stand-By Arrangement-Staff Report; Staff Supplement and Staff Statement; and Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2002)
This paper examines Turkey's Request for a Stand-By Arrangement (SBA). The program contains several measures to free up the growth potential of Turkey's private sector. The program rightly addresses key obstacles to domestic and foreign private investment. Although the program faces real risks, Turkey's policy record under the May 2001 program increases the likelihood of the new program being implemented as planned and achieving its key objectives. The IMF staff recommends the approval of the proposed SBA.